Psychology in the Sistema Único de Saúde of Porto Alegre:: Work Organization in Precarious Contexts - Peres Couto, Martina; Brandelli Costa, Angelo (Brazilian Journal of Mental Health, 2023)
Faced with the challenges of Psychology in adapting to new health care strategies, necessary for the performance with public policies, and the growing precariousness of the Unified Health System (SUS), this research sought to analyze the perceptions of professionals who are included in this work context. Based on the occupational health, semi-structured interviews were conducted with five psychologists who work in different services of the primary and secondary health care network in the city of Porto Alegre. Minayo's qualitative analysis was used to interpret the material, based on the Dejours Psychodynamic Theory. For this article, three categories of theme emerged: Organization and working conditions; Health care strategies; and Suffering at work. The analysis of the results shows a great disparity between the working model prescribed by public health policies and the real work. Issues such as disarticulation of the network and overload of tasks point to working conditions that generate suffering. The lack of institutional support provided in the policies and the deficiencies in training in Psychology contribute to the resistance of the category to overcome the clinical-individualist model. Individual actions and the enormous demand for care occupy the routine of services, keeping psychologists away from the spaces of work organization. Such action hinders the political positioning of the category, necessary to reinvent its practices and (re)act in a political context of dismantling public health.